Training in Child and Youth Mental Health: building knowledge with Multifunctional Resource Room teachers (Olhar de Professor, 2023)
The diversity that is present in the school context and the preparation of teachers to deal with such demands has been the subject of several studies on the field. In this sense, this report aims to present a proposal for continuing education on child and youth mental health carried out with teachers from multifunctional resource rooms linked to the public teaching network of two municipalities in the State of São Paulo, Brazil, which was developed from the prior identification of demands of teachers on the subject. The training was organized through in person and distance activities that totaled 30 hours, and addressed: mental health, child and youth mental health and psychological distress; risk and protective factors; school as a place of life and learning; action strategies at school; child and youth care network. It is concluded that offering tools so that teachers can deal with everyday demands can contribute to the advancement of school inclusion of children and adolescents in psychological distress.
Keywords: Teacher training. Child and Youth Mental Health. School inclusion.